2018
DOI: 10.1088/1367-2630/aae5c8
|View full text |Cite
|
Sign up to set email alerts
|

Surface termination dependent quasiparticle scattering interference and magneto-transport study on ZrSiS

Abstract: Dirac nodal line semimetals represent a new state of quantum matters in which the electronic bands touch to form a closed loop with linear dispersion. Here, we report a combined study on ZrSiS by density functional theory calculation, scanning tunnelling microscope (STM) and magneto-transport measurements. Our STM measurements reveal the spectroscopic signatures of a diamond-shaped Dirac bulk band and a surface band on two types of cleaved surfaces as well as a spin-polarized surface band at G at E∼0.6 eV on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 45 publications
5
15
0
Order By: Relevance
“…In Ref. 33, a linear in field component for the MR is observed for ZrSiS. Here, our modified-two-band model includes also a linear µ0H term.…”
Section: Supplementary Materialsmentioning
confidence: 80%
“…In Ref. 33, a linear in field component for the MR is observed for ZrSiS. Here, our modified-two-band model includes also a linear µ0H term.…”
Section: Supplementary Materialsmentioning
confidence: 80%
“…The QPI analysis around specified point defects can reveal a selective scattering. For example, in the topological nodal-line materials ZrSiS and ZrSiSe [27][28][29], two different types of point defects are found to selectively scatter electronic states of the floating surface band [30,31] and bulk band, respectively [31][32][33][34][35]. In ZrSiSe, both the surface and bulk bands were observed to be scattered by a single defect [31,32], which has not been detected yet in ZrSiS.…”
Section: Introductionmentioning
confidence: 95%
“…S1-S6 in the SM [42]. These are just the end points of the Dirac line-nodes along the X-R and A-M lines at the zone boundaries [30,43], which are protected by the glide mirror operation, as labeled by the red line in e.g., Fig. 4(a).…”
Section: A Electronic Band Structuresmentioning
confidence: 99%
“…For example, the recent studies on the SHE in the rutile oxide Dirac semimetals [26] and the TaAs Weyl semimetal family [27] showed that the anticrossing of the nodal points and nodal lines in these TSMs could be the sources of Among the Dirac semimetals, the studies of the ZrSiStype compounds have been particularly intense in the past few years. The members of the ZrSiS family share the same space group P 4/nmm (No.129), and they all possess the symmetry protected Dirac nodal features in the band structures [23,[28][29][30]. In addition, several exotic quantum phenomena such as highly anisotropic magnetoresistance [31], gapless Dirac surface states in topological crystalline insulator (TCI) phase [29], Shubnikovde Haas and de Haas-van Alphen oscillations [30,32], have been observed in some compounds of the family.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation